Act of treason - Flynn, Vince 1966-2013 (Pocket Books fiction., 2006)
When a presidential candidate wins the election through sympathy votes two weeks after a terrorist attack kills his wife, CIA operative Mitch Rapp investigates dangerous allegations about the attack's hidden agenda, a case that threatens the government's stability.